Empowerment Through Entrepreneurship: A Mixed-Methods Analysis of Social Grants and Economic Sufficiency - Thobeka Ncanywa; Ntsika Dyantyi; Abiola John Asaleye (Economies)
Entrepreneurship is crucial in promoting innovation, job creation, and poverty alleviation, particularly in developing economies. This study adopts a mixed-methods approach, using quantitative and qualitative analysis to examine macroeconomic factors’ impact on entrepreneurial activity. The quantitative analysis utilises fully modified least squares and dynamic ordinary least squares to estimate long-run relationships, while the qualitative component applies thematic analysis to assess the role of school-based gardening initiatives in promoting students’ economic participation. Our findings indicate that government expenditure on education significantly enhances entrepreneurship, whereas access to credit remains ineffective, suggesting persistent barriers in financial intermediation. Labour force participation shows a positive relationship with entrepreneurship, supporting the idea that a more engaged labour force promotes business creation. The findings also show a negative impact of regulatory quality on entrepreneurship, stressing the need for regulatory reforms to reduce entry barriers. While technology adoption has a delayed effect, long-term investments in digital infrastructure are recommended. At the micro-level, school-based entrepreneurship programs, such as vegetable gardening, cultivate entrepreneurial skills, though sustainability depends on consistent support and resources. Based on these findings, this study suggests the need to enhance education, improve access to finance, and streamline regulatory frameworks to promote entrepreneurship.